Predictive value of procalcitonin for the diagnosis of bowel strangulation - Ayten, R; Dogru, O; Camci, C; Aygen, E; Cetinkaya, Z; Akbulut, H (Wiley, 2005)
Intestinal obstruction is responsible for 3% of admissions to hospital emergency surgical departments, but it is difficult to distinguish simple obstruction from strangulation. Simple criteria for this distinction are sought. In this experimental study, procalcitonin, a known marker of bacterial inflammation, was used to detect strangulation. The predictive value of procalcitonin for small bowel strangulation was evaluated. Thirty male New Zealand rabbits (mean weight: 3.0 kg) were divided into three groups. In the first (control) group, only laparatomy was performed. In the second group, simple obstruction was created by ligating a 10-cm distal ileum segment. In the third group, distal strangulation was created by ligating a 10-cm distal ileum segment with the mesentery. Blood (I cc) was taken from the right auricular vein of each animal for measuring the procalcitonin level. In both the control group and the simple obstruction group the procalcitonin levels were normal. In the strangulation group, elevation of procalcitonin was detected after 30 minutes, and the elevation was statistically significant at 120th minute compared with the control and simple obstruction groups. In patients with small bowel obstruction, measurement of procalcitonin levels is easy to perform and can be used in the follow-up. A more extensive clinical study is needed to evaluate the accuracy of the test as a marker.
Keywords: Obstruction; Differentiation; Management; Ct